Taxonomic revision of the Neotropical ant genus Hylomyrma Forel, 1912 (Hymenoptera: Formicidae: Myrmicinae), with the description of fourteen new species - Ulysséa, Mônica Antunes; Brandão, C.r.f. (Zootaxa, 2021)
This paper provides a taxonomic revision of the Neotropical ant genus Hylomyrma Forel (1912) (Myrmicinae: Pogonomyrmecini). Morphological traits combined with geographical data and natural history information led to the recognition of 30 species, fourteen of them described here as new: Hylomyrma adelae sp. n., Hylomyrma dandarae sp. n., Hylomyrma jeronimae sp. n., Hylomyrma lispectorae sp. n., Hylomyrma lopesi sp. n., Hylomyrma macielae sp. n., Hylomyrma margaridae sp. n., Hylomyrma mariae sp. n., Hylomyrma marielleae sp. n., Hylomyrma mitiae sp. n., Hylomyrma peetersi sp. n., Hylomyrma primavesi sp. n., Hylomyrma virginiae sp. n. and Hylomyrma wachiperi sp. n. Lectotypes for H. speciosa (junior synonym of H. balzani) and H. reitteri are here designated from syntypes to improve nomenclatural stability. Except for the three species most recently described (H. montana, H. plumosa, and H. villemantae), the external morphology of workers is described or redescribed, as well as for the known males and queens, most described here for the first time. Of the 30 recognized species herein, 11 present intercastes; at least three of them present female specimens with queen-like traits that may be understood as ergatoids. An updated identification key for Hylomyrma workers is provided, as well as high resolution photographs of all known sexes and castes, species distribution maps, and a summary of what is known from the biology of all species.